Effectiveness of Ethno-Nationalist Based POGIL Model to Increase the Value of Patriotism and Discipline in Children - Suhari, Suhari; Panggestu, Ibnu Graha Ade; Azzahra, Harlanda Almaratus; Novtrisa, Rida; Listanto, Kinanda Pandu; Apra Santosa, Tomi (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2024)
The study aims to determine the effect of the ethno-nationalist-based Process Oriented Guided Inquiry Learning (POGIL) model to increase the value of patriotism and discipline in children through meta-analysis. The inclusion criteria in this study are a) research data obtained from Google Scholar; ERIC, ProQuest, Wiley, DOAJ and Springer, b) research must be indexed by SINTA, Scopus or journal indexing portals managed by the Ministry of Higher Education, Research and Technology equivalent to DOAJ, EBSCO and Index Copernicus, c) the topic must be relevant, d) research published in 2022-2024, e) research publications must have a value of (r), (t), or (F), f) research samples must be more than 25 children. The meta-analysis research uses the JASP application for data analysis. The results of the study concluded that there was a significant influence of the effectiveness of the Ethno-nationalist-Based Process Oriented Guided Inquiry Learning Model on the value of character of love for the homeland and discipline in children with a strong influence category (p< 0.001; rRE = 1.034). Furthermore, in this study, no publication bias was detected so that it can be scientifically accounted for. These findings show that the Effectiveness Model of Process Oriented Guided Inquiry Learning Based on Ethno-nationalism is effective in increasing the Character Values of Love for the Fatherland and Discipline in Children.